2011
DOI: 10.1007/s00231-011-0945-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of enhanced heat transfer by addition of CuO nanoparticle

Abstract: An energy storage system has been designed to study the thermal characteristics of paraffin wax with an embedded nano size copper oxide (CuO) particle. This paper presents studies conducted on phase transition times, heat fraction as well as heat transfer characteristics of paraffin wax as phase change material (PCM) embedded with CuO nanoparticles. 40 nm mean size CuO particles of 2, 5 and 10% by weight were dispersed in PCM for this study. Experiments were performed on a heat exchanger with 1.5-10 l/min of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(40 citation statements)
references
References 30 publications
1
38
0
1
Order By: Relevance
“…Jesumathy et al [73] developed an experimental setup and investigated the heat transfer characteristics of a vertical annulus energy storage system with paraffin dispersed with copper oxide nanoparticles. It was shown that the heat transfer coefficient of paraffin during the solidification was increased by 78% for the maximum flow rate of 10 L/min when the weight fraction of copper oxide particles was 10%, compared to that of the pure paraffin wax.…”
Section: Numerical and Experimental Investigation On Thermodynamic Bementioning
confidence: 99%
“…Jesumathy et al [73] developed an experimental setup and investigated the heat transfer characteristics of a vertical annulus energy storage system with paraffin dispersed with copper oxide nanoparticles. It was shown that the heat transfer coefficient of paraffin during the solidification was increased by 78% for the maximum flow rate of 10 L/min when the weight fraction of copper oxide particles was 10%, compared to that of the pure paraffin wax.…”
Section: Numerical and Experimental Investigation On Thermodynamic Bementioning
confidence: 99%
“…Recently, there has been a considerable interest to enhance the thermal conductivity of organic PCMs by addition of small amount of nanostructured materials [12][13][14][15][16]. Among these materials, carbon-based nanomaterials have been received more attention because of their anomalous thermal conductivity (~3000 W/m K) with respect to poor conductance of organic PCMs (~0.2 W/m K).…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that the thermal conductivities of the paraffin/nickel foam and the paraffin/copper foam composites were nearly three and 15 times larger than that of pure paraffin. Metal oxide fillers have also been used to improve the thermal conductivity of paraffin PCMs, but the enhancement is not significant [10][11][12][13]. For example, Wang et al [10] dispersed Al 2 O 3 nanoparticles with mass fractions of 1-5 wt % into paraffin (Tm = 52-56 • C) to prepare the composites.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the thermal conductivity of the composite with 5 wt % Al 2 O 3 was higher than pure paraffin by about 0.07 W/mK in the solid state at 288 K, and 0.05 W/mK in the liquid state at 338 K, respectively. Jesumathy et al [12] added 40 nm CuO particles into paraffin (Tm = 58 • C). The thermal conductivity was enhanced 6-7.8% in the liquid state, and the heat transfer coefficient during solidification was increased by about 78% for the maximum flow rate.…”
Section: Introductionmentioning
confidence: 99%